Assessment of risk and knowledge regarding non-communicable diseases among adult population: a cross-sectional study in the urban slums of West Bengal - Merin K. Jaison; Trina Sengupta; Sauryadripta Ghose; Vandana Majhi; Archismita Santra; Shashi Kumar M. (Discover Public Health)
Abstract Background Non-communicable diseases (NCDs) are a growing global public health challenge. Timely screening helps identify risk factors, enabling prevention and early treatment. This study assessed NCD risk and knowledge and identified associated factors in an urban slum population. Materials and Methods A community-based cross-sectional study was conducted among 165 participants aged ≥ 30 years in the urban slums of Kolkata, West Bengal, using two-stage cluster sampling. NCD risk was assessed using the Community-based Assessment Checklist (CBAC) questionnaire, which includes age, behavioural risk factors (tobacco, alcohol use, physical inactivity), waist circumference, and family history. Knowledge was evaluated through a pretested semi-structured questionnaire. Data were analysed using SPSS 25. Results Among participants, 35.8% had a high NCD risk, while 46.7% demonstrated good knowledge. Male gender (AOR 5.07, 95% CI 2.35–10.92) and lower socioeconomic status (AOR 3.00, 95% CI 1.11–8.11) were significantly associated with high NCD risk. Higher age (AOR 1.04, 95% CI 1.01–1.07) and education level (AOR 2.75, 95% CI 1.36–5.55) were linked to better knowledge. Conclusion This study underscores the need for targeted public health interventions in urban slums, where NCD risk is high. Male gender and lower socioeconomic status are key risk factors, while education enhances knowledge. Findings support strengthening India’s existing program on non-communicable diseases (NP-NCD) by integrating prevention into primary care, enhancing screening, and promoting community awareness to improve healthcare services in underserved areas.